A question of trust: military defection during regime crises in Benin and Togo. Issue 3 (3rd April 2018) - Morency-Laflamme, Julien
ABSTRACT: This article examines the role of trust between military officers and opposition forces in fostering mass defections of military personnel during pro-democracy uprisings. The current literature on military defection emphasizes the role of either opposition characteristics, or government control policies. Combining the two, however, takes better account of defection as an interaction between officers and the opposition. Through an analysis of civil–military relations during mass uprisings in Benin (1989–1990) and Togo (1990–1993), this article finds that loyalist stacking creates a core of military personnel with a strong stake in regime preservation, while counterbalancing leaves open the possibility for a military-opposition alliance. Alliance also depends on civic resistance campaign characteristics (the unity of the movement, its nonviolent character, the presence of opposition leaders with social ties to military personnel) and promises to military personnel that acknowledge the latter groups' interests. These findings provide a new theoretical framework for understanding military actions during regime crises.